(untitled) (Research, Society and Development, 2021)
Infection with the new Coronavirus 2019 (COVID-19) has had a serious impact on global health in the hospital and dental sectors. Brazil recorded the second highest number of patients and more deaths from coronavirus in the world, second only to the United States. The social and scientific media stated that dental surgeons were considered a risk group for COVID-19, and could act as a vector for direct and indirect transmission in their dental care routine. In view of the occurrence of new rules and habits supported by the World Health Organization, they warned about dental care and procedures to be carried out in case of extreme need; that is; only urgent and emergency care, and elective cases were postponed, as a measure to prevent the spread of COVID-19, the social distance adopted in Brazil can have economic and psychosocial consequences for dentistry. In this context, the present study, the authors conducted a national survey with Brazilian dentists to assess the impact of the New Coronavirus pandemic on dental activities. A total of 246 dentist surgeons responded to the survey and the results indicated that the vast majority of professionals had decreased income in the period, either by canceling appointments or decreasing the number of visits. They are aware that they are more exposed, and for this reason they made scientific investments and purchased individual protection equipment, and these combinations of factors can cause greater damage in the pandemic period.